Herbal Plant Farming Development Strategy - Eliyatiningsih, Eliyatiningsih; Erdiansyah, Iqbal; Kartika Sari, Vega; Nurahmanto, Dwi (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 17 No 1 (2023): Vol 17 No 1 (2023)DO - 10.24843/SOCA.2023.v17.i01.p02, 2023)
The demand for herbal plants has increased significantly in the last few years, especially during the covid 19 pandemic. People believe that herbal products have savors to maintain body immunity. The purpose of this study was to analyze internal factors (strengths and weaknesses) and external factors (opportunities and threats), formulate policies, and identify priority strategies that can be applied by farmers in developing herbal farming. This research had conducted in Pace Village, Silo District, Jember Regency, from August to November 2021. The analysis used internal and external factors analysis, SWOT matrix, and QSPM analysis to determine priority strategies. The internal and external factor analysis showed that herbal plant farming was in Region V with defend and maintain position. Based on the SWOT matrix, eight strategies had earned to develop a herbal business. Based on the QSPM analysis, the key strategy was to increase farmers' knowledge regarding the prospects and marketing of herbal plants, with a total value of 8.365